Biochemical evidence of defense response in paddy induced by bio-agents against brown leaf spot pathogen - and S.S.L. SRIVASTAVA, GIRDHARI LAL KUMAWAT, S.K. BISWAS* (Indian Phytopathology, 2008)
Pre-application of spore suspension of bioagents protected plant against challenge infection of Drechslera oryzae, showing reduction in disease severity in paddy from 59.21 to 12.40%. Biochemical analysis of treated leaves showed increased level of total soluble protein exhibited 11.19% - 85.21% and -10.06 to 66.57% and total phenol content from -8.62 to 79.31 and 9.43 - 96.23% over diseased and healthy plant respectively. Correlation co-efficient between soluble protein and disease severity showed negative correlation (r = -0.43 to -0.47). Similarly, total phenol content also showed negative correlation (r = -0.32 to -0.38) with disease severity. Increased amount of soluble protein and total phenol resulted from the activity of bio-agents indicated their involvement in the induction of host defense in paddy.